International Students’ Adjustment Problems and Behaviors - Gebhard, Jerry G. (Journal of International Students, 2012)
This article focuses on the kinds of adjustment problems that international students had while they studied at a university in the United States, as well as the adjustment behaviors they used when faced with these problems. Qualitative data was collected and analyzed for over a decade through on-going interviews with 85 international students, as well as through observation field notes and student-written narratives about their adaptation experiences. Findings show that students were challenged by academics, social interaction, and emotional reactions to their new life. To manage their problems, students made use of behaviors that can facilitate adapting to the new culture, as well as behaviors that can obstruct them from adapting. Facilitative behaviors include coping strategies, use of supportive people, observation and imitation, and reflection. Behaviors interpreted as impeding adaptation include expecting others to adapt, complaining, and withdrawing.